GNSS characterization of hydrological loading in South and Southeast Asia. Issue 3 (17th October 2020) - Materna, Kathryn; Feng, Lujia; Lindsey, Eric O; Hill, Emma M; Ahsan, Aktarul; Alam, A K M Khorshed; Oo, Kyaw Moe; Than, Oo; Aung, Thura; Khaing, Saw Ngwe; Bürgmann, Roland
SUMMARY: The elastic response of the lithosphere to surface mass redistributions produces geodetically measurable deformation of the Earth. This deformation is especially pronounced in South and Southeast Asia, where the annual monsoon produces large-amplitude hydrological loads. The Myanmar–India–Bangladesh–Bhutan (MIBB) network of about 20 continuously operating Global Navigation Satellite Systems (GNSS) stations, established in 2011, provides an opportunity to study the Earth's response to these loads. In this study, we use GRACE temporal gravity products as an estimate of long-wavelength surface water distribution and use this estimate in an elastic loading calculation. We compare the predicted vertical deformation from GRACE with that observed with GNSS. We find that elastic loading inferred from the GRACE gravity model is able to explain the phase and much of the peak-to-peak amplitude (typically 2–3 cm) of the vertical GNSS oscillations, especially in northeast India and central Myanmar. GRACE-based corrections reduce the RMS scatter of the GNSS data by 30–45% in these regions. However, this approach does not capture all of the seasonal deformation in central Bangladesh and southern Myanmar. We show by a synthetic test that local hydrological effects may explain discrepancies between the GNSS and GRACE signals in these places. Two independent hydrological loading models of water stored in soil, vegetation, snow, lakes and streams display phase lags compared to the GRACE and GNSS observations, perhaps indicating that groundwater contributes to the observed loading in addition to near-surface hydrology. The results of our calculations have implications for survey-mode GNSS measurements, which make up the majority of geodetic measurements in this region. By using the GNSS data together with estimates of hydrological loading from independent observations and models, we may be able to more accurately determine crustal motions caused by tectonic processes in South and Southeast Asia, while also improving our ability to monitor the annual monsoon and resulting water storage changes in the region.